2013
DOI: 10.1017/s1461145712000569
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity induced by the dopamine D2/D3 receptor agonist quinpirole is attenuated by inhibitors of endocannabinoid degradation in mice

Abstract: The present study was designed to investigate the effect of pharmacological inhibition of endocannabinoid degradation on behavioural actions of the dopamine D2/D3 receptor agonist quinpirole in male C57Bl/6J mice. In addition, we studied the effects of endocannabinoid degradation inhibition on both cocaine-induced psychomotor activation and behavioural sensitization. We analysed the effects of inhibition of the two main endocannabinoid degradation enzymes: fatty acid amide hydrolase (FAAH), using inhibitor URB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
(87 reference statements)
0
27
0
Order By: Relevance
“…This test is a widely used method to assess drug or non-drug induced changes in D 2 function (Tenk et al, 2007, Vorhees et al, 2009). Because quinpirole is a preferential D 2 receptor agonist, a higher level of motor activity under quinpirole challenge presumably reflects an upregulation of D 2 receptor function (Luque-Rojas, Galeano, 2013, Moreno et al, 2005), and is also thought to be mediated through an increase in the efficacy of the post-synaptic D 2 transduction (Szumlinski et al, 1997, Szumlinski et al, 2000). In our previous study on adult rats, we found that repeated risperidone treatment increased the quinpirole-induced hyperlocomotion: risperidone-treated rats exhibited a significantly higher level of motor activity than the vehicle-pretreated ones under the quinpirole (1.0 mg/kg, sc) challenge, suggesting that risperidone sensitization induced in adult rats is likely mediated by D 2 receptor upregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This test is a widely used method to assess drug or non-drug induced changes in D 2 function (Tenk et al, 2007, Vorhees et al, 2009). Because quinpirole is a preferential D 2 receptor agonist, a higher level of motor activity under quinpirole challenge presumably reflects an upregulation of D 2 receptor function (Luque-Rojas, Galeano, 2013, Moreno et al, 2005), and is also thought to be mediated through an increase in the efficacy of the post-synaptic D 2 transduction (Szumlinski et al, 1997, Szumlinski et al, 2000). In our previous study on adult rats, we found that repeated risperidone treatment increased the quinpirole-induced hyperlocomotion: risperidone-treated rats exhibited a significantly higher level of motor activity than the vehicle-pretreated ones under the quinpirole (1.0 mg/kg, sc) challenge, suggesting that risperidone sensitization induced in adult rats is likely mediated by D 2 receptor upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous and intermittent treatment doses of HAL were based on the rat striatal D 2 receptor occupancy data (65–80%) that corresponds to clinically relevant conditions (Kapur et al, 2003) and prior studies using the conditioned avoidance response task (Samaha, Reckless, 2008, Samaha, Seeman, 2007) and social behavior (Li et al, 2005). The doses of quinpirole (a selective dopamine D 2/3 receptor agonist) were chosen based on previous work showing that this dose was effectively induced hyperactivity, and to assess D 2 receptor-mediated motor activity (Gao and Li, 2013, Luque-Rojas et al, 2013, Nakamura et al, 1994, Qiao, Gao, 2014a). …”
Section: Methodsmentioning
confidence: 99%
“…This dose of PCP is shown to induce a robust hyperlocomotion effect without causing severe stereotypy (Gleason and Shannon, 1997; Kalinichev et al, 2008). The chosen quinpirole dose (1.0 mg/kg) targets post-synaptic D 2/3 receptors and causes an increase in motor activity (Koller et al, 1987; Luque-Rojas et al, 2013; Nakamura et al, 1994; Prosser et al, 1989). This dose of quinpirole was chosen based on the similar studies from our laboratory (Gao and Li, 2013; Qiao et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Doses of RIS (1.0 and 0.3 mg/kg, for drug test and challenge respectively) and ASE (0.2 and 0.1 mg/kg, for drug test and challenge respectively) were chosen on the basis of literature review showing that these doses produce a reliable disruption of avoidance responding and cause a sensitization effect [23, 34-39]. The chosen quinpirole dose (1.0 mg/kg) targets post-synaptic D 2 receptors and causes an increase in motor activity [29, 40-42]. …”
Section: Methodsmentioning
confidence: 99%
“…We also investigated the involvement of dopamine D 2 receptor as a biological mechanism underlying antipsychotic sensitization by comparing the quinpirole-induced increase in motor activity in drug-pretreated animals to vehicle-pretreated animals. Because quinpirole is a selective D 2/3 receptor agonist, a higher level of motor activity under quinpirole challenge presumably reflects an upregulation of D 2 receptor function [28, 29]. Quinpirole-induced hyperlocomotion is also thought to be mediated through an increase in the efficacy of the post-synaptic D 2/3 transductional mechanisms [30, 31], and has been widely used to assess drug or non-drug induced changes in D 2/3 functions [32, 33].…”
Section: Introductionmentioning
confidence: 99%